(untitled) (Research, Society and Development, 2021)
Computational thinking involves cognitive processes that seek to understand which problem can be solved and to develop possible solutions efficiently and creatively. Elderly people may have cognitive impairment due to age-related factors. Computational thinking is a suitable proposal to be applied at this stage of life. In this study, a systematic literature review is presented, whose objective was to identify the areas of knowledge in which computational thinking, with a focus on cognitive processes, is being applied to the elderly. The search was carried out in May 2021, in electronic databases provided by CAPES (CAFe access): Scopus, Web of Science, Scielo, Sbie, Eric, IEEE Xplore, Ovid, Science Direct, SpringerLink, SAGE Journals and Wiley Online Library. The literature search resulted in a total of 165 studies, and after the exclusion criteria, 6 studies remained for the qualitative synthesis. The research method used was PRISMA - Preferred Reporting Items for Systematic Reviews and Meta-Analyses. The results point to the presence of computational thinking in different areas. Its use had very positive aspects when it has its focus on elderly people. The main finding of the analyzed studies indicates that the use of computational thinking by elderly people has a relevant role for cognitive stimulation.